Cataract Surgery under Local Anaesthesia - Search for Safer One (Delta Medical College Journal, 2018)
Background: Cataract surgery is usually done under local anaesthesia. But till now there are no absolutely safe local anaesthetics. Current study is done to find out a safer local anaesthetic for cataract surgery.Objective: To evaluate the onset, duration, quality, side effects and safety of bupivacaine and lignocaine in peribulbar block (PBB) for cataract surgery.Materials and method: This was a randomized observational controlled clinical study done in Monno Medical College Hospital, Manikganj, Bangladesh, in the period of October, 2014 to October, 2015. Two hundred cataract patients attending ophthalmology department were allocated to receive either 4 mL 0.5% bupivacaine+4 ml 2% lignocaine or 8 mL of 2% lignocaine for peribulbar block during cataract surgery. Onset, duration, quality of anaesthesia and after effects were used as a clinical parameter for the study.Results: Mean anaesthetic durations of lignocaine and bupivacaine+lignocaine were 75 minutes and 120 minutes respectively. Least complications were observed in subjects with lignocaine.Conclusion: Peribulbar blocks with 2% lignocaine provide better anaesthesia for cataract surgery and success rates are high without any complications. Anaesthetic time of lignocaine alone is enough for cataract surgeryDelta Med Col J. Jan 2018 6(2): 68-72